The importance of peace in Norberto Bobbio's thematic trilogy - José Francisco de Assis Dias (2024)
The central theme of the present study is the importance of "Peace" in Norberto Bobbio's thematic trilogy, namely: Democracy, Human Rights, and Peace, as interconnected and necessary elements for historical and social progress. The objective is to explore the interaction between Democracy, Human Rights, and Peace, advocated by Bobbio, and its significance for the construction of a just and peaceful society. The relationship between Democracy, Human Rights, and Peace as essential components of a historical movement towards social progress will be discussed; the doctrines justifying war will be analyzed, and their validity in the atomic age will be questioned; the necessary conditions to achieve Peace, including non-aggression pacts and the establishment of rules for the peaceful resolution of conflicts, will be highlighted; the lack of authority of the United Nations (UN) and the need for an "effective international power" to guarantee global peace will be examined. The study of Bobbio's thematic trilogy is relevant to understanding the importance of the interaction between Democracy, Human Rights, and Peace in the pursuit of a just and peaceful society. Moreover, the analysis of doctrines justifying war and the necessary conditions to achieve Peace contributes to a critical reflection on contemporary challenges related to global security and Human Rights. The study is based on the analysis of Norberto Bobbio's writings on Democracy, Human Rights, and Peace, examining his ideas and arguments throughout his extensive body of work. The research involves a theoretical and critical approach, interpreting Bobbio's major contributions on these topics. The results highlight the interdependence between Democracy, Human Rights, and Peace, emphasizing their relevance for social and historical progress. Furthermore, the research underscores the need to rethink doctrines justifying war in the atomic age and the importance of establishing an effective international authority to promote global peace.